Positive electrode active material and lithium ion secondary battery

By using lithium-iron composite fluoride as the positive electrode active material and adjusting its composition ratio, the shortcomings of lithium-ion secondary batteries in high voltage operation are solved, and the effects of high energy density and low resource risk are achieved.

CN119905577APending Publication Date: 2025-04-29HONDA MOTOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411495549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-10-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The Fe-based positive electrode active substances in existing lithium-ion secondary batteries have insufficient operation in high voltage, resulting in low energy density and high resource risk.

Method used

Li-iron composite fluoride is used as the main component of the positive electrode active material, and the molar ratio of lithium to iron (x is within the range of 0.5 < x < 1.5) is adjusted to increase the average discharge voltage and achieve high voltage operation.

Benefits of technology

It realizes high voltage operation of lithium-ion secondary batteries, improves energy density, and reduces resource risks, and has the advantage of low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905577A_ABST
    Figure CN119905577A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: an Fe-based positive electrode active material capable of high-voltage operation; and a lithium ion secondary battery comprising the positive electrode active material. In addition, the positive electrode active material and the lithium ion secondary battery contribute to energy efficiency. A positive electrode active material having a lithium-iron complex fluoride as a main component, the lithium-iron complex fluoride being represented by Formula 1: LixFeF (3 + x) (in Formula 1, x is a number satisfying 0.5 < x < 1.5).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium ion secondary battery. Background Art

[0002] In recent years, in order to ensure that more people can use appropriate, reliable, sustainable and advanced energy, research and development of secondary batteries that contribute to energy efficiency are being carried out. In particular, lithium-ion secondary batteries are becoming increasingly important as a power source for electric vehicles (EVs), hybrid electric vehicles (HEVs), etc.

[0003] Positive electrode active materials have attracted attention as an important component that determines the capacity of lithium-ion secondary batteries, and their development is being promoted. As positive electrode active materials used in lithium-ion secondary batteries, for example, iron (Fe)-based lithium iron phosphate (LiFePO4) is known to have low resource risk. LiFePO4 has excellent cycle characteristics and safety, but low voltage and small capacity, so compared with the nickel (Ni) and cobalt (Co)-based materials used in the past, the energy density (voltage × capacity) expressed as the product of voltage and capacity is small. In order to build a small battery, an electrode material with high energy density is required. In order to achieve high energy density, high voltage operation of the battery is important.

[0004] In order to increase the voltage of batteries using materials containing elements with low resource risk, it is expected to use expensive transition metals (e.g., Rather ). However, Fe 4+ Very unstable, turns into Fe due to side reaction 3+ , or Fe 4+ It requires a lot of energy and sometimes cannot be generated. 3+ Compounds used as positive electrode active materials may not necessarily be able to operate at high voltages.

[0005] For example, Non-Patent Document 1 reports that by using iron fluoride (FeF3), LiFeF3 is generated during charge and discharge, and the average discharge voltage is 3.1 V. Non-Patent Document 2 reports that LiFeO2 can be expected to have a high energy density. Prior art literature Non-patent literature

[0006] Non-patent document 1: F. Badway, et al., "Carbon Metal Fluoride Nanocomposites" J. Electrochem. Soc., 150 (10) A1318-A1327 (2003) Non-patent document 2: Y.Hu, et al., "A Simple, Quick and Eco-Friendly Strategy ofSynthesis Nanosized α-LiFe02 Cathode with Excellent ElectrochemicalPerformance for Lithium-Ion Batteries" Materials, 11, 1176 (2018) Summary of the invention Technical problem to be solved by the invention

[0007] In Non-Patent Document 2, the actual voltage is about 2.5 V, which is lower than the expected voltage. The average discharge voltage (3.1 V) in Non-Patent Document 1 is also lower than the voltage of LiFePO4, and there is room for improvement in order to further increase the voltage.

[0008] The present invention is completed to solve the above-mentioned technical problems, and its purpose is to provide an Fe-based positive electrode active material capable of high voltage operation and a lithium ion secondary battery containing the positive electrode active material. In addition, the resource risk is reduced, which helps to reduce the cost. Technical solutions for solving technical problems

[0009] In order to achieve the above-mentioned object, the present invention provides the following means. [1] A positive electrode active material, wherein the main component is lithium iron composite fluoride, The lithium iron composite fluoride is represented by the following formula (1): Li x FeF (3+x) (1) In formula (1), x is a number satisfying 0.5<x<1.5.

[0010] [1] The positive electrode active material has a high average discharge voltage and can operate at a high voltage. Therefore, in a lithium ion secondary battery including the positive electrode active material, the number of batteries required can be reduced, contributing to cost reduction.

[0011] [2] The positive electrode active material according to [1], wherein in the above formula (1), x satisfies 0.6≤x≤1.0.

[0012] [2] The positive electrode active material can further increase the average discharge voltage and can operate at a higher voltage, thus contributing to further cost reduction.

[0013] [3] The positive electrode active material according to [1] or [2], wherein in the X-ray diffraction pattern, there are peaks in the range of 20°≤2θ<25° and in the range of 25°≤2θ≤30°.

[0014] [3] The positive electrode active material concerned has a peak derived from the crystal structure of FeF3 and a peak derived from the crystal structure of LiFe2F6.

[0015] [4] A lithium ion secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode contains the positive electrode active material according to any one of [1] to [3].

[0016] [4] The positive electrode of the lithium ion secondary battery contains the positive electrode active material according to any one of [1] to [3]. This means that the battery can operate at a high voltage.

[0017] [5] The lithium ion secondary battery according to [4], wherein the dQ / dV plot during discharge in the charge and discharge cycle has a peak value in the range of 3.77 V to 4.0 V.

[0018] [5] The lithium-ion secondary battery mentioned here means that the positive electrode active material undergoes a chemical reaction in a high voltage range of 3.77 V to 4.0 V. This means that the battery can operate at a higher voltage.

[0019] [6] The lithium ion secondary battery according to [4] or [5], wherein the peak height of 3.77 V to 4 V is 1.2 to 4.4 times the peak height of 3.3 V to 3.5 V in the dQ / dV plot during discharge in the charge and discharge cycle.

[0020] [6] The lithium-ion secondary battery mentioned here means that the positive electrode active material undergoes a chemical reaction in a high voltage range of 3.77 V to 4.0 V. This means that the battery can operate at a higher voltage.

[0021] [7] The lithium ion secondary battery according to any one of [4] to [6], wherein the average discharge voltage is 3.8V to 4.0V.

[0022] [7] The average discharge voltage of the lithium ion secondary battery is as high as 3.8 V to 4.0 V. This means that it can operate at a high voltage.

[0023] [8] The lithium ion secondary battery according to any one of [4] to [7], wherein the electrolyte is a liquid electrolyte, a solid electrolyte or a semisolid electrolyte.

[0024] [8] The lithium-ion secondary battery described herein can be applied to any of liquid electrolytes, solid electrolytes, or semi-solid electrolytes, and can therefore be applied to various batteries.

[0025] [9] The lithium ion secondary battery according to any one of [4] to [8], wherein the negative electrode is metallic lithium or graphite.

[0026] [9] The lithium-ion secondary battery described above can also be applied to batteries whose negative electrodes are metal lithium or graphite, and thus can be applied to various batteries. Effects of the Invention

[0027] According to the present invention, it is possible to provide an Fe-based positive electrode active material capable of high voltage operation and a lithium ion secondary battery including the positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a diagram showing an X-ray diffraction pattern of a positive electrode active material according to one embodiment of the present invention. Figure 2 It is a cross-sectional view schematically showing a lithium ion secondary battery according to one embodiment of the present invention. Figure 3 This is a graph showing a charge and discharge curve in a charge and discharge cycle of a lithium ion secondary battery according to an embodiment of the present invention. Figure 4 Yes means Figure 3 A graph showing the dQ / dV curve during the charge and discharge cycle. Figure 5 This is a graph showing a dQ / dV plot during a charge and discharge cycle of a lithium ion secondary battery according to another embodiment of the present invention. Figure 6 The graph shows the X-ray diffraction patterns of the positive electrode active materials of Examples 1 to 5 and Comparative Example 1. Figure 7 This is a graph showing the charge and discharge curves of a lithium ion secondary battery containing the positive electrode active material of Example 1. Figure 8 This is a graph showing the charge and discharge curves of a lithium ion secondary battery containing the positive electrode active material of Example 2. Fig. 9 This is a graph showing the charge and discharge curves of a lithium ion secondary battery containing the positive electrode active material of Example 3. Fig.10 This is a graph showing the charge and discharge curves of a lithium ion secondary battery containing the positive electrode active material of Example 4. Fig.11This is a graph showing the charge and discharge curves of a lithium ion secondary battery containing the positive electrode active material of Example 5. Fig.12 This is a graph showing the charge and discharge curves of a lithium ion secondary battery containing the positive electrode active material of Comparative Example 1. Fig.13 Yes means Figure 7 A graph showing the dQ / dV curve during the charge and discharge cycle. Fig.14 Yes means Figure 8 A graph showing the dQ / dV curve during the charge and discharge cycle. Fig.15 Yes means Fig. 9 A graph showing the dQ / dV curve during the charge and discharge cycle. Fig.16 Yes means Fig.10 A graph showing the dQ / dV curve during the charge and discharge cycle. Fig.17 Yes means Fig.11 A graph showing the dQ / dV curve during the charge and discharge cycle. Fig.18 Yes means Fig.12 A graph showing the dQ / dV curve during the charge and discharge cycle. DETAILED DESCRIPTION

[0029] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0030] [Positive electrode active material] The positive electrode active material of the present embodiment is lithium iron composite fluoride as the main component, and is used for the positive electrode of a lithium ion secondary battery. The lithium iron composite fluoride "as the main component" means that the content of lithium iron composite fluoride is 75% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 99% by mass or more, and can also be 100% by mass, relative to the total mass of the positive electrode active material. As long as the function of the present invention is not impaired, the positive electrode active material may also contain components other than the main component.

[0031] The positive electrode active material of the present embodiment may contain only one type of lithium iron complex fluoride, or may contain two or more types of lithium iron complex fluorides, as long as the main component is lithium iron complex fluoride.

[0032] In the case of manufacturing a positive electrode active material with lithium iron composite fluoride as the main component, the overall composition ratio (Li:Fe:F) of the lithium iron composite fluoride is also maintained in the obtained positive electrode active material. When the positive electrode active material obtained with lithium iron composite fluoride having such a composition as the main component is used in a secondary battery, high voltage operation can be achieved. In addition, the composition ratio of the lithium iron composite fluoride can be adjusted to be the same as the composition ratio required for the desired positive electrode active material.

[0033] (Lithium Iron Complex Fluoride) The lithium iron composite fluoride of the present embodiment is represented by the following formula (1). Li x FeF (3+x) (1) In formula (1), x is a number satisfying 0.5<x<1.5. In formula (1), x is preferably 0.6≤x≤1.2, more preferably 0.6≤x≤1.0, and further preferably 0.7≤x≤1.0. If x is within the above numerical range, the average discharge voltage can be increased, and operation can be performed at a higher voltage. Therefore, a small battery with a high energy density can be constructed.

[0034] In formula (1), x represents the molar ratio of Li to Fe. The molar ratio of Li to Fe is x:1. In addition, the molar ratio of Li, Fe and F is x:1:(3+x). The composition of lithium iron composite fluoride can be determined by inductively coupled plasma (ICP) emission spectrometry.

[0035] <X-ray diffraction (XRD) pattern> Figure 1 In the figure, as an example of the X-ray diffraction (XRD) pattern of the positive electrode active material of this embodiment, the XRD pattern of Example 4 described later is shown. Figure 1 As shown, the positive electrode active material of this embodiment preferably has peaks in the range of 20°≤2θ<25° and in the range of 25°≤2θ≤30°. The peak in the range of 20°≤2θ<25° represents a peak derived from the crystal structure of FeF3 as trivalent iron. The peak in the range of 25°≤2θ≤30° represents a peak derived from the crystal structure of LiFe2F6. This means that the positive electrode active material of this embodiment has the same crystal structure as FeF3 and LiFe2F6. The lithium iron composite fluoride of this embodiment has a composition ratio of LiFeF4, and iron is entirely composed of Fe 3+ Therefore, if it is described according to the composition formula of LiFe2F6 of the space group P42 / mnm tetragonal system, it becomes the following formula (2). Li y Fe2F (6+y) (2) In formula (2), y is a number satisfying 1<y<3.

[0036] [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode contains a positive electrode active material having the above-mentioned lithium iron composite fluoride as a main component. The lithium ion secondary battery of this embodiment may include other battery elements as needed.

[0037] The lithium ion secondary battery of this embodiment can directly adopt the battery elements of known lithium ion secondary batteries except that the positive electrode contains the positive electrode active material with the above-mentioned lithium iron composite fluoride as the main component. The lithium ion secondary battery of this embodiment can be any structure in coin type, button type, cylindrical type, square type, and laminated type. In addition, the lithium ion secondary battery of this embodiment can be applied to a wide range of uses such as mobile devices such as mobile phones and notebook computers, and in-vehicle use.

[0038] Hereinafter, the lithium ion secondary battery of the present embodiment will be described as a lithium ion secondary battery (coin-type lithium ion secondary battery) using an electrolyte. The battery elements described below can also be similarly applied to all-solid lithium ion secondary batteries and semi-solid lithium ion secondary batteries that do not use an electrolyte.

[0039] like Figure 2 As shown, the lithium ion secondary battery 1 of the present embodiment includes a negative electrode can (negative electrode terminal) 20 , a negative electrode 3 , a separator 4 impregnated with an electrolyte, an insulating spacer (gasket) 5 , a positive electrode 2 , and a positive electrode can 10 .

[0040] The positive electrode can 10 is arranged on the lower side of the separator 4, and the negative electrode can 20 is arranged on the upper side of the separator 4, and the positive electrode can 10 and the negative electrode can 20 form the outer shape of the lithium ion secondary battery 1. Between the positive electrode can 10 and the negative electrode can 20, the positive electrode 2 and the negative electrode 3 are arranged via the separator 4 impregnated with the electrolyte, and the positive electrode 2 and the negative electrode 3 are separated by the separator 4. The positive electrode can 10 and the negative electrode can 20 are electrically insulated by the insulating gasket 5.

[0041] The lithium ion secondary battery 1 can prepare the positive electrode 2 by mixing a conductive agent, a binder, etc. with the positive electrode active material of the present embodiment as needed to prepare a positive electrode composite material, and press-bonding the composite material to a current collector (not shown). As the current collector, a stainless steel mesh, aluminum foil, etc. can be preferably used. As the conductive agent, carbon nanotube (CNT), acetylene black, Ketjen black, etc. can be preferably used. As the binder, tetrafluoroethylene, polyvinylidene fluoride, etc. can be preferably used.

[0042] The combination of the positive active material, the conductive agent and the binder in the positive electrode composite material is not particularly limited. The content of the positive active material in the positive electrode composite material is preferably 75% by mass to 100% by mass, and more preferably 90% by mass to 99% by mass. The content of the conductive agent in the positive electrode composite material is preferably 1% by mass to 15% by mass, and more preferably 0.1% by mass to 5% by mass. The content of the binder in the positive electrode composite material is preferably 0.1% by mass to 10% by mass, and more preferably 0.1% by mass to 5% by mass.

[0043] In the lithium ion secondary battery 1, as the negative electrode 3 relative to the positive electrode 2, for example, metal lithium, lithium alloy and other metal-based materials, graphite (graphite), MCMB (mesophase carbon microbeads) and other carbon-based materials, silicon (Si), Si alloys, silicon oxide and other silicon-based materials can be used as known materials that function as negative electrode active materials and can embed and release lithium. Among them, as the negative electrode 3, metal lithium and graphite are preferred.

[0044] The separator 4 and the battery container (positive electrode can 10 and negative electrode can 20 ) can adopt known battery elements.

[0045] As the electrolyte, it is possible to use a known electrolyte, a semi-solid electrolyte, a solid electrolyte, etc. As the electrolyte, for example, it is possible to use an electrolyte obtained by dissolving an electrolyte such as lithium perchlorate or lithium hexafluorophosphate in a solvent such as ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), or diethyl carbonate (DEC).

[0046] As the semisolid electrolyte or solid electrolyte, in addition to using the above-mentioned positive electrode active material containing lithium iron composite fluoride as a main component, a known semisolid electrolyte or solid electrolyte can be used. As a semi-solid electrolyte, for example, an electrolyte composed of a polymer component and a standard electrolyte solution can be cited. As the above-mentioned polymer component, for example, polyvinylidene fluoride (PVDF) / polyethylene oxide (PEO), polyacrylonitrile (PAN) / PEO, polymethyl methacrylate (PMMA), PVDF / hexafluoropropylene (HFP), etc. can be cited. As the above-mentioned standard electrolyte solution, for example, 1mol / L lithium hexafluorophosphate (LiPF6) EC / DMC solution, 1mol / L LiPF6 EC / ethyl methyl carbonate (EMC) solution, 1mol / LLiPF6 EC / DMC / EMC solution, etc. can be cited.

[0047] In the case of an all-solid-state lithium-ion secondary battery, as the electrolyte, for example, a polymer solid electrolyte such as a polyethylene oxide-based polymer compound, a polymer compound containing at least one of a polyorganosiloxane chain or a polyoxyalkylene chain, a sulfide solid electrolyte, an oxide solid electrolyte, or the like can be used.

[0048] The positive electrode of the all-solid lithium ion secondary battery can be made, for example, by having a positive electrode composite material containing a solid electrolyte in addition to the above-mentioned positive electrode active material, conductive agent, and binder supported on a positive electrode collector such as aluminum, nickel, or stainless steel.

[0049] The lithium ion secondary battery 1 of the present embodiment can operate at a high voltage because the positive electrode 2 contains the positive electrode active material of the present embodiment.

[0050] <dQ / dV plot of charge and discharge cycle> Figure 3 In FIG. 1 , a graph related to Example 4 described later is shown as an example of a charge and discharge curve in a charge and discharge cycle of the lithium ion secondary battery of the present embodiment. Figure 3 The horizontal axis of the graph represents the capacity of the lithium ion secondary battery. Figure 3 The vertical axis of the graph represents the voltage of the lithium-ion secondary battery during charge and discharge. Figure 3 In the charge and discharge curves of , the upper right curve represents the curve during charging, and the upper left curve represents the curve during discharging. Figure 3 The 1st, 2nd, 3rd, and 4th represent the number of charge and discharge cycles.

[0051] Figure 3 The capacity of the lithium ion secondary battery shown is 30 mAh / g, and the voltage of the curve when the capacity is half of 15 mAh / g is the average discharge voltage. Figure 3 The average discharge voltage of the lithium ion secondary battery of this embodiment is about 3.8V.

[0052] Figure 4 Shown in Figure 3 The dQ / dV curve during the charge and discharge cycle. Figure 4 The horizontal axis of the graph represents the voltage during the charge and discharge cycle. Figure 4 The vertical axis of the curve shows the voltage versus Figure 3 The value obtained by differentiating the capacitance (dQ / dV plot, dQdV -1 Draw a line). Figure 4 The upward convex curve represents the curve during charging, and the downward convex curve represents the curve during discharging. Figure 4 The 1st, 2nd, 3rd, and 4th represent the number of charge and discharge cycles.

[0053] like Figure 4As shown, the curve during charging has peaks at 3.85V and 4.1V. The curve during discharging has peaks at 3.77V and 4.0V. These peaks indicate that a chemical reaction has occurred in the positive electrode active material at the positive electrode during charging or discharging. This indicates that a chemical reaction has occurred in the high voltage range of 3.77V to 4.0V during discharging, indicating that the lithium-ion secondary battery can operate at a high voltage.

[0054] exist Figure 5 In FIG. 1 , a graph related to Example 1 described later is shown as an example of a dQ / dV plot in a charge and discharge cycle of a lithium ion secondary battery according to another embodiment. Figure 5 The upward convex curve represents the curve during charging, and the downward convex curve represents the curve during discharging. Figure 5 The 1st, 2nd, 3rd, and 4th represent the number of charge and discharge cycles.

[0055] The discharge curve of Example 1 has peaks at 3.5 V, 3.77 V, and 4.0 V. The dQ / dV value of the peak at 3.5 V is -0.0708 mAhg -1 V -1 The peak dQ / dV value at 3.77V is -0.090mAhg -1 V -1 The peak dQ / dV value at 4.0V is -0.1634mAhg -1 V -1 . It should be noted that the dQ / dV value of each peak value represents the average value of three charge and discharge cycles except the initial cycle. The peak value of 3.77V is -0.090 / -0.0708=1.27 times the peak value of 3.5V, and the peak value of 4.0V is -0.1634 / -0.0708=2.31 times the peak value of 3.5V. It should be noted that in the discharge curve of Example 3 described later, the dQ / dV value of the peak value at 3.5V is -0.107mAhg -1 V -1 The peak dQ / dV value at 4.0V is -0.464mAhg -1 V -1 . In Example 3, the peak height of 4.0V is -0.464 / -0.107=4.34 times higher than the peak height of 3.5V. Thus, the curves during discharge in Example 1 and Example 3 are 1.2 to 4.4 times higher than the peak height of 3.3V to 3.5V, and the peak height of 3.77V to 4.0V is 1.2 to 4.4 times higher. This indicates that during discharge, the chemical reaction at 3.77V to 4.0V occurs at 1.2 to 4.4 times the mass of the chemical reaction at 3.3V to 3.5V, and the lithium-ion secondary battery is capable of high voltage operation.

[0056] The average discharge voltage of the lithium ion secondary battery of this embodiment is preferably 3.8V to 4.0V, and more preferably 3.8V to 3.9V. If the average discharge voltage of the lithium ion secondary battery is above the above lower limit, it can be operated at a higher voltage. The upper limit of the average discharge voltage of the lithium ion secondary battery is not particularly limited, and is substantially 4.0V.

[0057] [Method for producing positive electrode active material] The positive electrode active material of this embodiment contains the above-mentioned lithium iron composite fluoride as a main component. As the lithium source of the lithium iron composite fluoride, halides such as lithium fluoride (LiF), hydroxides such as lithium hydroxide monohydrate (LiOH·H2O), carbonates such as lithium carbonate (Li2CO3), acetates such as lithium acetate (CH3COOLi) and lithium acetate dihydrate (CH3COOLi·2H2O) can be used without special restrictions.

[0058] As the iron source of the lithium iron composite fluoride, trivalent iron is preferred to divalent iron, and iron fluoride (FeF 3 ) is more preferred, from the viewpoint of enabling high voltage operation.

[0059] When manufacturing lithium iron composite fluoride, the above-mentioned lithium source and iron source are mixed and mechanically treated for a given time and under given conditions. For example, when lithium fluoride is used as the lithium source and trivalent iron (FeF3) is used as the iron source, it is believed that the compound represented by the above formula (1) can be obtained by the following reaction. LiF+FeF3→LiFeF4 (compound with x=1 in the above formula (1))

[0060] The value of x in the compound represented by the above formula (1) can be adjusted by the molar ratio of LiF to FeF 3 .

[0061] The specific means used in the mechanical treatment are not particularly limited, and various means conventionally used for the purpose of crushing and mixing solid materials can be applied. Among these means, a ball mill is preferred, and a planetary ball mill is more preferred from the aspect of being able to fully crush and mix the raw materials.

[0062] The mechanical treatment time is, for example, preferably 8 to 12 hours, more preferably 9 to 11 hours. As conditions for the mechanical treatment, the rotation speed is preferably 250 rpm to 450 rpm, more preferably 300 rpm to 400 rpm. The temperature during the mechanical treatment is not particularly limited, and the mechanical treatment can be performed at room temperature (eg, 5° C. to 30° C.). The atmosphere during the mechanical treatment is preferably an inert gas (a rare gas such as argon (Ar) or nitrogen (N 2 ) gas, etc.).

[0063] After mechanical treatment to obtain the compound represented by formula (1), from the viewpoint of improving capacity and rate characteristics, it is preferred to carbon-coat the compound represented by formula (1) by crushing and mixing with carbon particles. As carbon particles, for example, carbon nanotubes (CNT), acetylene black, Ketjen black, etc. can be used. Among these carbon particles, CNT is preferred from the viewpoint of further improving the conductivity of the positive electrode active material.

[0064] The pulverization and mixing conditions during carbon coating can be the same as those for the mechanical treatment described above.

[0065] By using the obtained positive electrode active material as a positive electrode to produce a lithium ion secondary battery, a battery that operates at a high voltage can be obtained. Example

[0066] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.

[0067] [Example 1] (Li 0.6 FeF 3.6 (Preparation of the compound wherein x=0.6 in the formula (1)) 0.439 g of iron fluoride (FeF3) and 0.0606 g of lithium fluoride (LiF) were mechanically treated using a planetary ball mill. The planetary ball mill used was a Premium line PL-7 manufactured by Fritsh. The jar and the grinding balls were made of zirconium oxide, and 50 g of grinding balls with a diameter of 5 mm were used in a 45 mL jar. The treatment conditions for the mechanical treatment were 350 rpm and 10 hours. Then, 0.55 g of carbon nanotubes (CNTs) were added to the jar and further mechanically treated to obtain a positive electrode active material. The treatment conditions for the mechanical treatment when obtaining the positive electrode active material were Ar atmosphere, 25°C, 350 rpm, and 10 hours.

[0068] The obtained positive electrode active material was subjected to X-ray diffraction measurement under the following measurement conditions. The results are shown in Figure 6 . 《X-ray diffraction measurement conditions》 X-ray diffraction device: Rigaku, SmartLab X-ray source: CuKα rays The opening angle of the incident parallel slit: 5.0° The length of the incident length limiting slit: 5.0 mm The opening angle of the light receiving parallel slit: 5.0° Kβ filter: Use Step size: 0.01° Entrance slit: 1 / 6° Light receiving slit 1: 4.0mm Light receiving slit 2: 13mm

[0069] like Figure 6 As shown, it can be seen that the diffraction patterns of the obtained positive electrode active material are consistent with those of DB card number 00-061-0194 space group R-3c, trigonal FeF3 and DB card number 01-074-2193 space group P42 / mnm, tetragonal LiFe2F6, and have the same crystal structure as FeF3 and LiFe2F6.

[0070] [Example 2] (Li 0.7 FeF 3.7 (Preparation of the compound wherein x=0.7 in the formula (1)) A positive electrode active material was obtained in the same manner as in Example 1, except that 0.431 g of iron fluoride (FeF 3 ) and 0.0693 g of lithium fluoride (LiF) were mechanically treated using a planetary ball mill. The obtained positive electrode active material was subjected to X-ray diffraction measurement under the same conditions as in Example 1. The results are shown in Figure 6 . like Figure 6 As shown, it can be seen that the diffraction patterns of the obtained positive electrode active material are consistent with those of DB card number 00-061-0194 space group R-3c, trigonal FeF3 and DB card number 01-074-2193 space group P42 / mnm, tetragonal LiFe2F6, and have the same crystal structure as FeF3 and LiFe2F6.

[0071] [Example 3] (Li 0.8 FeF 3.8 (Preparation of the compound wherein x=0.8 in the formula (1)) A positive electrode active material was obtained in the same manner as in Example 1, except that 0.422 g of iron fluoride (FeF 3 ) and 0.078 g of lithium fluoride (LiF) were mechanically treated using a planetary ball mill. The obtained positive electrode active material was subjected to X-ray diffraction measurement under the same conditions as in Example 1. The results are shown in Figure 6 . like Figure 6As shown, it can be seen that the diffraction patterns of the obtained positive electrode active material are consistent with those of DB card number 00-061-0194 space group R-3c, trigonal FeF3 and DB card number 01-074-2193 space group P42 / mnm, tetragonal LiFe2F6, and have the same crystal structure as FeF3 and LiFe2F6.

[0072] [Example 4] (Preparation of LiFeF4 (compound wherein x=1.0 in formula (1))) A positive electrode active material was obtained in the same manner as in Example 1, except that 0.407 g of iron fluoride (FeF 3 ) and 0.0934 g of lithium fluoride (LiF) were mechanically treated using a planetary ball mill. The obtained positive electrode active material was subjected to X-ray diffraction measurement under the same conditions as in Example 1. The results are shown in Figure 6 . like Figure 6 As shown, it can be seen that the diffraction patterns of the obtained positive electrode active material are consistent with those of DB card number 00-061-0194 space group R-3c, trigonal FeF3 and DB card number 01-074-2193 space group P42 / mnm, tetragonal LiFe2F6, and have the same crystal structure as FeF3 and LiFe2F6.

[0073] [Example 5] (Li 1.2 FeF 4.2 (Preparation of the compound wherein x=1.2 in the formula (1)) A positive electrode active material was obtained in the same manner as in Example 1, except that 0.391 g of iron fluoride (FeF 3 ) and 0.108 g of lithium fluoride (LiF) were mechanically treated using a planetary ball mill. The obtained positive electrode active material was subjected to X-ray diffraction measurement under the same conditions as in Example 1. The results are shown in Figure 6 . like Figure 6 As shown, it can be seen that the diffraction patterns of the obtained positive electrode active material are consistent with those of DB card number 00-061-0194 space group R-3c, trigonal FeF3 and DB card number 01-074-2193 space group P42 / mnm, tetragonal LiFe2F6, and have the same crystal structure as FeF3 and LiFe2F6.

[0074] [Comparative Example 1] (Preparation of LiFeF3) A positive electrode active material was obtained in the same manner as in Example 1, except that 0.392 g of ferrous fluoride (FeF 3 ) and 0.108 g of lithium fluoride (LiF) were mechanically treated using a planetary ball mill. The obtained positive electrode active material was subjected to X-ray diffraction measurement under the same conditions as in Example 1. The results are shown in Figure 6 . like Figure 6 As shown, it can be seen that the obtained positive electrode active material has a diffraction pattern consistent with that of LiFe2F6 of DB card number 01-074-2193 space group P42 / mnm and tetragonal system, and has the same crystal structure as LiFe2F6.

[0075] [Manufacturing of lithium-ion secondary batteries] (Production of positive electrode) 80 parts by mass of the positive active material obtained in Examples 1 to 5 and Comparative Example 1, 10 parts by mass of acetylene black, and 10 parts by mass of polyvinylidene fluoride were dispersed in N-methylpyrrolidone as a solvent to prepare a slurry (positive electrode composite material) containing 80% by mass of the positive active material, 10% by mass of acetylene black, and 10% by mass of polyvinylidene fluoride as a solid component. The slurry was applied to an aluminum foil, pressed at 15 tons, and punched with a punch having a diameter of 10 mm to prepare a positive electrode. At this time, the mass of the positive active material was adjusted to 3.5 mg.

[0076] (Manufacturing of coin-type batteries) The prepared positive electrode (diameter 10mm) is placed on the positive electrode can, a porous polyethylene film is placed on it as a separator, and it is pressed with a polypropylene gasket. Then, a Li negative electrode with a thickness of 0.5mm is placed, and a spacer for thickness adjustment is placed. Then, as a non-aqueous electrolyte solution, a mixed solvent (volume ratio 5:5) of ethylene carbonate and diethyl carbonate obtained by dissolving 1mol / L of lithium hexafluorophosphate is added between the positive electrode can and the negative electrode, and it is impregnated in the separator, the negative electrode can is placed and sealed, and a coin-type battery (lithium ion secondary battery) is made.

[0077] [Evaluation of battery performance] The battery performance was evaluated using the produced coin-shaped batteries. Specifically, the produced coin-shaped batteries were charged and discharged at a constant current value of 5 mA / g per mass of the positive electrode active material. The upper limit voltage during constant current charging and discharging was set to 4.25 V, and the lower limit voltage was set to 3.35 V. The rest time after charging and discharging was 10 minutes. The charge and discharge capacity (mAh / g) was calculated per unit mass of the positive electrode active material. The charge and discharge curves of constant current charging and discharging of Examples 1 to 5 and Comparative Example 1 are shown in Figures 7 to 12 .

[0078] The energy densities of Examples 1 to 5 to which the present invention is applied are 113Wh / kg, 136Wh / kg, 175Wh / kg, 108Wh / kg, and 119Wh / kg, respectively. Figures 7 to 11 As shown, the average discharge voltages of Examples 1 to 5 to which the present invention is applied are 3.76 V, 3.79 V, 3.73 V, 3.79 V, and 3.72 V. Thus, it can be confirmed that Examples 1 to 5 to which the present invention is applied have high energy density and average discharge voltage, and can achieve high energy density and high voltage operation. In contrast, the energy density of Comparative Example 1 (LiFeF3) in which the positive electrode active material does not contain the compound represented by formula (1) is 87Wh / kg. Fig.12 As shown, the average discharge voltage is 3.64V.

[0079] Based on the obtained charge and discharge curve, the horizontal axis is the voltage, and the vertical axis is the value obtained by differentiating the capacity with the voltage (dQ / dV, dQdV -1 ), a dQ / dV plot was made, and the voltage at which the chemical reaction occurred (reaction voltage) was obtained based on the peak voltage of the dQ / dV plot during discharge. The dQ / dV plots of Examples 1 to 5 and Comparative Example 1 are shown in Figures 13 to 18 .

[0080] like Figures 13 to 17 As shown, it can be confirmed that the peak voltage of the dQ / dV plot during discharge in Examples 1 to 5 to which the present invention is applied is as high as 3.77 V to 4.0 V, and that a chemical reaction occurs at a high voltage inherent in the compound represented by formula (1). In contrast, Fig.18 As shown, in Comparative Example 1 (LiFeF3) in which the positive electrode active material does not contain the compound represented by formula (1), the peak voltage of the dQ / dV plot during discharge is not observed near 4V, and only a broad peak is shown in the operating voltage range. 2+ / Fe 3+ In order to obtain a clear reaction, it is necessary to lower the lower limit of the operating voltage range. It is believed that in Comparative Example 1, a chemical reaction occurred at a voltage lower than the lower limit voltage of 3.35 V in this embodiment.

[0081] From the above results, it is clear that according to the present invention, it is possible to provide an Fe-based positive electrode active material capable of high voltage operation and a lithium ion secondary battery including the positive electrode active material. Description of Reference Numerals

[0082] 1 Lithium-ion secondary battery 2 Positive electrode 3 Negative electrode 4 Isolation 5. Insulation pad (gasket) 10 positive electrode tank 20 Negative can (negative terminal).

Claims

1. A positive electrode active material, wherein: The positive electrode active material is mainly composed of lithium iron composite fluoride. The lithium iron composite fluoride is represented by the following formula 1: <h2 style=";text-align:left;direction:ltr">1: Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> FeF<h2 style=";text-align:left;direction:ltr"> (3+x) In Formula 1, x is a number satisfying 0.5<x<1.

5.

2. The positive electrode active material according to claim 1, wherein In the above formula 1, x satisfies 0.6≤x≤1.

0.

3. The positive electrode active material according to claim 1, wherein The X-ray diffraction pattern has peaks in the range of 20°≤2θ<25° and in the range of 25°≤2θ≤30°.

4. A lithium ion secondary battery, wherein: The lithium ion secondary battery comprises a positive electrode, a negative electrode, and an electrolyte, and the positive electrode contains the positive electrode active material according to any one of claims 1 to 3.

5. The lithium ion secondary battery according to claim 4, wherein: The dQ / dV plot during discharge in the charge and discharge cycle has a peak value in the range of 3.77V to 4.0V.

6. The lithium ion secondary battery according to claim 4, wherein: The peak value of 3.77V to 4.0V at the dQ / dV plot line during discharge in the charge and discharge cycle is 1.2 to 4.4 times higher than the peak value of 3.3V to 3.5V.

7. The lithium ion secondary battery according to claim 4, wherein: The average discharge voltage is 3.8V~4.0V.

8. The lithium ion secondary battery according to claim 4, wherein The electrolyte is a liquid electrolyte, a solid electrolyte or a semi-solid electrolyte.

9. The lithium ion secondary battery according to claim 4, wherein: The negative electrode is metallic lithium or graphite.